Is the Item-Position Effect in Achievement Measures Induced by Increasing Item Difficulty?. Issue 5 (3rd September 2017) - Zeller, Florian; Reiß, Siegbert; Schweizer, Karl
Abstract : This work examines the hypothesis that the arrangement of items according to increasing difficulty is the real source of what is considered the item-position effect. A confusion of the 2 effects is possible because in achievement measures the items are arranged according to their difficulty. Two item subsets of Raven's Advanced Progressive Matrices (APM), one following the original item order, and the other one including randomly ordered items, were applied to a sample of 266 students. Confirmatory factor analysis models including representations of both the item-position effect and a possible effect due to increasing item difficulty were compared. The results provided evidence for both effects. Furthermore, they indicated a substantial relation between the item-position effects of the 2 APM subsets, whereas no relation was found for item difficulty. This indicates that the item-position effect stands on its own and is not due to increasing item difficulty.